Solution for Unclaimed Funds in Banks: An Islamic Economic Perspective - Hashri, Miqdam Awwali; Fatwa, Nur (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
Natural disasters that have occurred and resulted in quite a large number of victims include Aceh (2004) and Palu Sigi Donggala (2018). The inevitable loss of life in the event of a disaster causes unclaimed funds to settle in the bank because the owner of the account balance and their heirs are victims of a natural disaster, or their whereabouts are unknown. In previous studies, the handling of unclaimed funds in the banking system was carried out in three ways: left alone, resolved by returning to the owner, and becoming bank income. Meanwhile, according to the Fatwa contained in the Compilation of Sharia Economic Law, a custodian of property/muwaddi' funds or the custodian of assets/funds is not known, then the mustaudi' or those entrusted with the assets/funds shall keep the object of the assets/funds until it is known and/or proven that the muwaddi' has passed away. This study uses a literacy study method to solve the problem of unclaimed funds' property rights. Therefore, it is necessary to clarify the concept of property rights of unclaimed funds so that they can be managed by parties or institutions authorized to manage them and used for the benefit of the people.